2013
DOI: 10.1111/cen.12206
|View full text |Cite
|
Sign up to set email alerts
|

What predicts adverse outcomes in untreated primary hyperparathyroidism? The Parathyroid Epidemiology and Audit Research Study (PEARS)

Abstract: Baseline PTH, rather than calcium, best predicts long-term outcomes in untreated PHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 29 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…5,12,13 Kidney function (creatinine levels) and total alkaline phosphatase (a nonspecific marker for bone turnover) were not predictors of long-term outcome in the present study. 14 In accordance with PTH as the major predictor of outcome in the present study, 14 previous studies have demonstrated that PTH was directly correlated with bone turnover and thereby bone mass in PHPT, 5 as PTH was correlated with arterial stiffness 10 and left ventricular mass in the mild form of the disease. 9 Although PHPT is a chronic and stable disease with confirmed increased risk of CVD and CVD-related mortality, it is still highly debatable whether surgical treatment of the uncomplicated milder cases is of benefit for the patients.…”
supporting
confidence: 87%
“…5,12,13 Kidney function (creatinine levels) and total alkaline phosphatase (a nonspecific marker for bone turnover) were not predictors of long-term outcome in the present study. 14 In accordance with PTH as the major predictor of outcome in the present study, 14 previous studies have demonstrated that PTH was directly correlated with bone turnover and thereby bone mass in PHPT, 5 as PTH was correlated with arterial stiffness 10 and left ventricular mass in the mild form of the disease. 9 Although PHPT is a chronic and stable disease with confirmed increased risk of CVD and CVD-related mortality, it is still highly debatable whether surgical treatment of the uncomplicated milder cases is of benefit for the patients.…”
supporting
confidence: 87%
“…In a retrospective population based observational study of mild PHPT patients (PEARS), selected from a cohort between 1997 and 2006, both cardiovascular morbidity and mortality ratio appeared to be increased (114), contrary to several studies carried out before the '90 (115,116). These authors, in an effort to identify the best biochemical risk factors alongside other factors for predicting adverse outcomes in untreated PHPT patients showed that calcium was associated with increased risk of all-cause mortality in the short term but had no significant impact on other outcomes, while baseline PTH, rather than calcium, best predicts long-term outcomes (117). Thus, the question remains unresolved as to which of the two, i.e.…”
Section: Primary Hyperparathyroidism and Mortality For Cardiovascularmentioning
confidence: 88%
“…Further, Yu et al [46] have also recently observed that baseline calcium levels were not significantly related to fatal cardiovascular disease or non-fatal cardiovascular disease in PHPT. However, serum PTH rather than serum calcium appeared to be associated with an increased risk of fatal and non-fatal cardiovascular disease.…”
Section: Presentationmentioning
confidence: 99%